2004
DOI: 10.1021/jp0477405
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanism of Dimethyl Ether Oxidation to Formaldehyde on Supported Molybdenum Oxide Domains

Abstract: Kinetic isotope effect and isotopic tracer/exchange methods were combined with in situ infrared spectroscopy and kinetic data to determine the mechanism of dimethyl ether (DME, CH 3 OCH 3 ) oxidation to formaldehyde (HCHO) on MoO x /Al 2 O 3 . The reaction intermediates and elementary steps established a redox mechanism that led to kinetic rate equations that are consistent with observed dependencies of reactant pressures. Methoxide concentrations as detected by in situ infrared spectroscopy correlated directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…16 Figure 3). DTBP forms protonated structures that bind irreversibly, thus rendering Brønsted acid sites inaccessible for catalysis; these molecules cannot coordinate to Lewis acid sites, because access to the N-atom is hindered by the vicinal tert-butyl groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Figure 3). DTBP forms protonated structures that bind irreversibly, thus rendering Brønsted acid sites inaccessible for catalysis; these molecules cannot coordinate to Lewis acid sites, because access to the N-atom is hindered by the vicinal tert-butyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows ODH and DME formation rates (per POM) from CH 3 OH-O 2 reactants on H 3 PMo/SiO 2 (0. 16) before and during titration with DTBP (433 K, 4 kPa CH 3 OH, 20 kPa O 2 , 7 Pa DTBP), measured using procedures described in sections 2.2 and 2.3. Both rates decreased monotonically with increasing DTBP uptakes; saturation uptakes fully suppressed DME formation and led to a marked decrease in ODH rates (∼20% of initial rates at saturation; Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The coordination complex decomposes giving a mixture of ethanol, diethyl ether and ethylene below 130°C and mainly ethylene above 130°C. Dimethyl ether (DME), which is of interest as a suitable diesel fuel, has been extensively studied by Iglesia et al [16][17][18][19][20] on supported MoOx and VOx domains and by Solymosi et al [21][22][23] on metal surfaces. Basically these studies show that the C-O-C moiety of DME breaks on the surface leaving methoxide in the case of oxide surfaces and methoxide and methyl in the case of metals.…”
Section: Introductionmentioning
confidence: 99%
“…Our kinetic study showed that the reaction is pseudo-zero order with respect to both dimethyl ether and oxygen molecule, suggesting that the reaction of the surface intermediate CH 3 O* is likely to be the rate-determining step [5]. DME dissociation over Mo-O sites was recently investigated by 18 O and H-D isotopic tracers and it was revealed that the oxy-dehydrogenation of CH 3 O* could not be the rate-determining step [8]. The HCHO/ CH 3 OH ratio in the products was closely related to the concentrations of DME and O 2 in a certain range in the feed stream.…”
Section: Introductionmentioning
confidence: 84%